Genetic impact of CDHR3 on the adult onset of asthma and COPD. Issue 11 (23rd July 2020) - Shigemasa, Rie; Masuko, Hironori; Hyodo, Kentaro; Kitazawa, Haruna; Kanazawa, Jun; Yatagai, Yohei; Iijima, Hiroaki; Naito, Takashi; Saito, Takefumi; Hirota, Tomomitsu; Tamari, Mayumi; Sakamoto, Tohru; et al.
Summary: Background: Adult‐onset asthma and chronic obstructive pulmonary disease (COPD) are heterogeneous diseases caused by complex gene‐environment interactions. A functional single nucleotide polymorphism of cadherin‐related family member 3 (CDHR3), known as a receptor of rhinovirus‐C, is associated with childhood‐onset asthma especially in atopic individuals. Objective: Here, we identified risk factors for adult‐onset asthma and COPD, focusing on the impact of the CDHR3 variant in atopic individuals. Methods: We conducted a longitudinal, retrospective, observational cohort study of 1523 healthy adults with baseline examinations at Tsukuba Medical Center Hospital in 2008 and retrospectively identified new‐onset, physician‐diagnosed asthma or COPD from 2009 to 2018. We assessed risk factors by the Cox regression analysis. The impact of CDHR3 variant rs6967330 was also examined in individuals with pre‐existing atopy. Results: Over 10 study years, 103 people developed airway diseases (79 asthma and 24 COPD; 52 females, average onset‐age 55 years old, range 38‐80). Higher body mass index (BMI) and lower forced expiratory volume in one second/forced vital capacity (FEV1 /FVC) ratio were significant risk factors (BMI: HR 1.072 [95% CI 1.005‐1.14], P =  .034; FEV1 /FVC ratio: HR 1.091 [1.044‐1.14], P =  .00011). Restriction to atopic individuals saw the A allele at rs6967330 and lower FEV1 /FVC ratio to associate with adult‐onset disease (A allele: HR 2.89 [1.57‐5.20], P =  .00062; FEV1 /FVC ratio: HR 1.10 [1.04‐1.17], P =  .0010). Conclusion and clinical relevance: Genetic susceptibility to rhinovirus‐C infection in atopic individuals is a risk factor for chronic airway diseases even in later life.